The "scramble" for the Arctic - protection of the marine mammals. Increasing activity, increasing noise, increasing threats – legal regulation - Balounová, Eva, 1989- (2014)
Due to the loss of the sea ice, Arctic area is opening for the offshore oil and gas development and for the shipping. There are many legal problems connected with these activities – the question of the extended continental shelf is essential for the legal title to the oil and gas developing in that area. The shipping in Arctic is also increasing, of course, with the oil and gas development it will increase even more. Both these activities – shipping and oil and gas development are connected with great environmental risks. The problem of oil spill is huge, but not the only one. These activities also bring man-made noise pollution to these waters. In Arctic area, there live marine mammals and especially some of them are dependent on the sounds they make and hear in order to communicate, find food, avoid predators, and navigate. Increasing man-made noise means threat for these mammals. In my thesis I focus on the legal regulation of the shipping and oil and gas development and especially on the regulation of the noise from these activities. Because the legal regulation is not very developed, I explain the regulation of these activities in general and also the legal framework of protection of the marine mammals. Then I try to find possibilities how to strengthen the legal regulation, and I also try to explain what are the possible scenarios for the development of the legislative in order to strengthen the protection of the Arctic area as a whole.